Confocal Microscopy for High‐Resolution and High‐Content Analysis of the Cell Cycle. Issue 1 (1st October 2014) - Furia, Laura; Pelicci, Piergiuseppe; Faretta, Mario
Abstract: Optical fluorescence microscopy offers a wide range of technological solutions to address many questions in biomedical research. Spatial resolution has been greatly improved by the use of confocal microscopes, providing a 3‐D analysis of the intracellular space. Automation has contributed to make confocal analysis available for high‐content image cytometry studies. However, the storage, browsing, and analysis of the amount of data generated can challenge the feasibility of such studies. Presented in this chapter is a multistep acquisition and analysis protocol that can bypass such difficulties by an analysis‐driven data collection. Cell‐cycle analysis of low‐resolution data can be employed to select cell populations of interest that can then be imaged at extremely high resolution and subjected to high‐content analysis. Curr. Protoc. Cytom . 70:7.42.1‐7.42.14. © 2014 by John Wiley & Sons, Inc.